Mortality Alphitobius diaperinus (Panzer) (Coleoptera: Tenebrionidae) by neem and citronella oils - Marques, Camila Renata Gonçalves; Mikami, Adriana Yatie; Pissinati, Aline; Piva, Leonardo Boiani; Santos, Odair José Andrade Pais; Ventura, Maurício Ursi (Semina: Ciências Agrárias, 2013)
The effects of neem oil and citronela essential oil, alone or associated on Alphitobius diaperinus (Panzer) were studied. Three bioassays were achieved. For the first study, treatments were neem oil (1, 3, 5, 7 and 9%.) and control (water). In the second bioassay, treatments were citronella oil (5, 10 15 and 20%) emulsified with coconut soap and control [coconut soap and water (10g / L)]. For the third bioassay, treatments were neem oil and citronella essential oil (1 and 3%), associated or not. After treatment, the insects were kept in an environmental chamber. Assessments of insect mortality were performed on the first, fifth and tenth day after spraying. In general, the highest mortality occurred 24 hours after spraying. Cumulative mortality was 59% and 81% for neem (9%) and for citronella oil, respectivelly. the highest mortality occurred when the oils were applied mixed. The type of interaction of the control agents on the mortality was additive.